2021
DOI: 10.13005/bbra/2870
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome of Two Different Honeybee Workers Subspecies In Saudi Arabia.

Abstract: Honeybees play a vital role in the world’s food supply by acting as essential pollinators in the agricultural fields. Interestingly, more than one third of the world’s essential crops are honeybee’s dependant. The adult honeybeeworkers harbour a simple specific bacterial spectrum in their guts with vital role in bees’ health. Gut microbial diversity of adult honeybee workerswasstudied through targeting the V3 and V4 regions of the 16S rRNA geneviaIllumina MiSeq. The study identified four phyla of the gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Apis mellifera jementica, a Saudi native, has been used in the majority of apiculture because it withstands local stressful conditions better than imported bees, especially in the summer when air temperatures soar (Alqarni et al, 2011a). Recently, Alatawy et al (2020) identified Lactobacillus and Bifidobacterium in the gut of Saudi Apis mellifera jementica (Alatawy et al, 2021). A lot of research carried out in different parts of the world also found LAB in bee stomachs (Olofsson et al, 2014;Aween et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Apis mellifera jementica, a Saudi native, has been used in the majority of apiculture because it withstands local stressful conditions better than imported bees, especially in the summer when air temperatures soar (Alqarni et al, 2011a). Recently, Alatawy et al (2020) identified Lactobacillus and Bifidobacterium in the gut of Saudi Apis mellifera jementica (Alatawy et al, 2021). A lot of research carried out in different parts of the world also found LAB in bee stomachs (Olofsson et al, 2014;Aween et al, 2012).…”
Section: Introductionmentioning
confidence: 99%